Shallow Nonlinear Bragg Grating for High Intensity Application - H. Alatas; A.A. Iskandar; M.O. Tjia (Indonesian Journal of Physics, 2003)
A study of shallow nonlinear Bragg grating with large intensity enhancement has been carried out using the standard couple mode theory. We show that for a sufficient intensity enhancement, the nonlinear modulation effect should not be neglected. We study the existence of gap solitons and show that the nonlinear modulation terms do affect their profiles.